Isolation and characterization of two different 5S rDNA in Anguilla anguilla and in Anguilla rostrata: Possible markers of evolutionary divergence - PICHIRI, GIUSEPPINA; NIEDDU, MARIELLA; CONI, PIERPAOLO; SALVADORI, SUSANNA; Manconi, S.; Casu, C.; Mezzanotte, R. (Molecular Ecology Notes, 2006)
We cloned and sequenced the Hae III 350-bp 5S ribosomal DNA (rDNA) band of Anguilla rostrata and designed specific primers from this sequence. Polymerase chain reaction performed with these primers is able to distinguish DNA samples obtained from European ( Anguilla anguilla ) and American ( Anguilla rostrata ) eels. Two amplicons of 1200 bp and 600 bp were obtained, respectively, from A. rostrata and A. anguilla, and the whole 5S rDNA repeated unit from these eels was cloned and sequenced. Southern blot experiments, using four different restriction enzymes and the 5S nontranscribed spacers regions as probe, are able to point out specific diversity in these eels.